2021
DOI: 10.7717/peerj-cs.719
|View full text |Cite
|
Sign up to set email alerts
|

Decoders configurations based on Unet family and feature pyramid network for COVID-19 segmentation on CT images

Abstract: Coronavirus Disease 2019 (COVID-19) pandemic has been ferociously destroying global health and economics. According to World Health Organisation (WHO), until May 2021, more than one hundred million infected cases and 3.2 million deaths have been reported in over 200 countries. Unfortunately, the numbers are still on the rise. Therefore, scientists are making a significant effort in researching accurate, efficient diagnoses. Several studies advocating artificial intelligence proposed COVID diagnosis methods on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…It can achieve accurate pixel-level segmentation with less data. Thus, UNet++ is widely applied in the field of medical image segmentation, such as Bacillus anthracis [ 6 ], leukocytes [ 13 ], COVID-19 [ 15 ]. This study did not use the method of data enhancement, randomly split the data set for training, the results showed that the average IoU can reach 95.41%.…”
Section: Discussionmentioning
confidence: 99%
“…It can achieve accurate pixel-level segmentation with less data. Thus, UNet++ is widely applied in the field of medical image segmentation, such as Bacillus anthracis [ 6 ], leukocytes [ 13 ], COVID-19 [ 15 ]. This study did not use the method of data enhancement, randomly split the data set for training, the results showed that the average IoU can reach 95.41%.…”
Section: Discussionmentioning
confidence: 99%
“…Semantic segmentation (SS) is an essential component in image processing and computer vision. SS has multiple applications, such as scene understanding ( Hofmarcher et al, 2019 ), autonomous driving ( Feng et al, 2020 ), and medical image analysis ( Liu et al, 2020 ; Abedalla et al, 2021 ; Nguyen et al, 2021 ), among many others. The goal of SS is to change the representation of an image into something more meaningful and easier to analyze using post-processing algorithms.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional semantic segmentation approaches that utilize this architectural style are SegNet ( Badrinarayanan, Kendall & Cipolla, 2017 ), U-Net ( Ronneberger, Fischer & Brox, 2015 ; Nguyen et al, 2021 ), DeepLab ( Chen et al, 2017 ), etc . The encoder element in this architecture consists of the pre-trained classification network that extracts the compound semantic features.…”
Section: Related Workmentioning
confidence: 99%